(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2025)
The study evaluates the structural deformation and changes in air permeability in plain-woven and ripstop parachute canopy fabrics stitched at 0° and 45° seam angles under repetitive impact loading. Results indicate that specimens with 0° seam angles are highly deformed at seam lines after a single impact load and cause a significant change in air permeability. These specimens experience complete damage at the seam lines after 3 to 4 impact loading cycles. Ripstop fabric demonstrates greater dimensional stability for a 45° seam angle, while plain-woven fabric shows higher recoverability during and after relaxing from repetitive impact load cycles. The findings reveal that air permeability increases at seam lines with successive impact loading cycles. Additionally, the plain-woven fabric samples exhibit higher air permeability and increments in permeability compared to ripstop fabric samples under repeated impact loading cycles.